Genomic Sequencing: Techniques, Advancements, and the Path Ahead - Mohsina Patwekar; Faheem Patwekar; A Venkata Badarinath; Abdul Ajeed Mohathasim Billah; Vamseekrishna Gorijavolu; Karthickeyan Krishnan; Palani Shanmugasundaram; P. Dharani Prasad; A. A. Kazi (Journal of Bio-X Research)
The development of genomic sequencing technology, from conventional techniques to state-of-the-art inventions, has greatly improved our understanding of genetic material. This review examines important advancements in sequencing techniques and how they have revolutionized genomics research. High-throughput capabilities made possible by next-generation sequencing (NGS) have enabled quick and affordable genomic analysis. Digital gene expression profiling was made possible by methods such as serial analysis of gene expression (SAGE), whereas long-read capabilities without amplification were analyzed by single-molecule sequencing, as demonstrated by Oxford Nanopore’s nanopore-based sequencing and PacBio’s single-molecule real-time (SMRT) technology. Synthetic long-read sequencing is one example of a hybrid technique that enhances genome assembly. New techniques, such as epigenetic sequencing, have revealed that DNA alterations are essential for gene control, and spatial transcriptomics has connected gene expression to tissue-specific patterns. Target analysis and knowledge of microbial ecosystems were further enhanced via the use of sophisticated techniques, including metagenomics and CRISPR-Cas9-based sequencing. When combined, these techniques allow researchers to examine microbial communities, transcriptome diversity, genomic structure, and epigenetic changes with new clarity. For example, single-cell sequencing has shown molecular heterogeneity between cells, and long-read sequencing has revealed intricate isoform variants. Personalized medicine has advanced owing to spatial transcriptomics, which targets gene expression in specific organs. Digital sequencing has also improved the sensitivity of mutation identification, transforming the diagnosis of the disease. The convergence of sequencing technologies has ushered in a new era of genomic studies, opening the door to groundbreaking findings in ecology, biology, and medicine. Future developments will improve knowledge of human genetics by further improving sequencing accuracy, affordability, and applicability.